SCHWARZ, FW Inventory of documents - SCHWARZ, FW (ARCA, 2018)
Born in Germany and immigrated to SA in 1933 where he served several congregations of the Baptist Church (1933-1958); Since 1958 he gave scriptural instruction at the Strydom Training College in Thaba 'Nchu
COVERAGE 1932-1974; 1.40 metre
Keywords: SCHWARZ, FW; Baptist Church; Communism; Apartheid